2013
DOI: 10.13172/2052-9287-1-1-447
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and impacts of occupational injury in healthcare workers: A critical review

Abstract: IntroductionThe high-risk, fast-paced healthcare industry presents unique health and safety challenges for healthcare personnel, including exposure to psychological and physical demands resulting in the incidence of musculoskeletal injuries of epidemic proportions. The dynamic healthcare environment demonstrates that workers are prone to injury through a host of factors unique to them being directly involved in patient care. Just as heredity and environment interact to result in disease, no single risk factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…This trend is similar to the findings of Mogale, Malangu, and Huma's () which reported that 73% of the healthcare providers in South Africa, in which STFIs had happened, were women (Mogale et al., ). In other studies, this proportion reached 80% (Miller, ; Yeoh, Lockhart, & Wu, ). However, most healthcare providers in different countries are women and this can explain the high proportion of women involved.…”
Section: Discussionmentioning
confidence: 72%
“…This trend is similar to the findings of Mogale, Malangu, and Huma's () which reported that 73% of the healthcare providers in South Africa, in which STFIs had happened, were women (Mogale et al., ). In other studies, this proportion reached 80% (Miller, ; Yeoh, Lockhart, & Wu, ). However, most healthcare providers in different countries are women and this can explain the high proportion of women involved.…”
Section: Discussionmentioning
confidence: 72%
“…There has been a scant amount of research focusing on workplace safety in home health care and particularly when it comes to examining the linkages between nursing and safety. Furthermore, the published studies provide insufficient information in terms of examining the view of nurses on HHC safety (Balize et al, 2012;Miller, 2013). This represents a legitimate gap in the existing literature.…”
Section: Life: International Journal Of Health and Life-sciences Issn 2454-5872mentioning
confidence: 99%
“…Other factors, any attribute or characteristic of exposure (individual, organizational, or environmental), can increase home-based DCWs’ risk of experiencing work-related injuries (Gropelli & Corle, 2011; Miller, 2013). Worker-specific risk factors for occupational injury include workers’ demographics, including their socioeconomic characteristics and work-related skills and knowledge (Oliver, Cheyne, Tomas, & Cox, 2002).…”
Section: Occupational Injury Patterns and Perceived Training Qualitymentioning
confidence: 99%